A relação entre o contraditório e a fundamentação das decisões no processo civil do Estado democrático de direito - Santos Junior, Sândalo Vianna dos (2013)
It examines the relationship between the contradictory reasons for decisions and axis as necessary methodological adequacy of civil procedure in a democratic state. The goal is to give the process a participatory nature, collaborative, communicative, argumentative, rational and capable of delivering results through endowed with democratic legitimacy. It is used as a theoretical discourse theory of Jürgen Habermas. Initially we investigated the basis of the connection title, peering up the neoconstitutionalism, the rule of law, democracy and fundamental rights theory. It is extracted that the process needs to conform to the constitutional notion of due process, which are the fundamental rights of appeal and the reasons for decisions. Analysis contingent the contradictory conclusion that they cover the rights of information and of reaction; parity of arms; active participation, ensuring influence and the banning of surprise decision, as well as the duty to cooperate, leading to procedural subjects a duty dialog. The contradictory radiates through the whole process being found in previous methods, postponed or deferred, and possible. As to reasons for decisions, it must analyze and resolve debates about the issues of fact and law, considering the reasons for the decision, the arguments discussed. Features and functions endoprocessuais extraprocessuais that allow control of the course and the end of the process and should justify the ruling, so that it is rationally acceptable, ie legitimate. After, deepens the bond between the adversarial and reasons for decisions from multiple perspectives, weaving up generic links, demonstrative, semantics and pragmatics; argumentative; communication; axiological and teleological; democratic, and complementarity. That nexus is indispensable to a civil permeated by participation, by dialogue, intersubjective communication, cooperation, and by rational argument, giving it a cogent democratic legitimacy. At the end, are placed in situations application of legal technique in which the tie-contradictory reasons for decisions serves as a parameter to the appropriate results to the notion of a democratic state.